KORELASI KARAKTERISTIK MIGREN DAN DISABILITAS AKIBAT MIGREN DENGAN KEJADIAN DEPRESI - Vonny Fibrianty Goenawan, Henny Anggraini Sadeli (Neurona Majalah Kedokteran Neuro Sains, 2009)
INTRODUCTION MIGRAINE IS A HIGHLY PREVALENT HEADACHE DISORDER THAT HAS A SUBSTANSIAL IMPACT ON THE INDIVIDUAL SOCIETY AND THE FAMILY MIGRAINE IS ASSOCIATED WITH SIGNIFICANT MORBIDITY STUDIES HAVE DEMOSTRATED AN ASSOCIATION BETWEEN MIGRAINE AND DEPRESSION BUT CHARACTERISTICS OF MIGRAINE THAT ASSOCIATED WITH DEPRESSION HAS NOT CLEARLY UNDERSTOOD AND STUDIES BEFORE HAD INVESTIGATED SEPARATELY